DAYA ADSORPSI KARBON AKTIF DARI KULIT SALAK (Salaccazalacca) UNTUK MENURUNKAN KADAR ASAM LEMAK BEBAS PADA MINYAK GORENG CURAH - Adiansyah Adiansyah; Yosy Cinthya Eriwaty Silalahi (Jurnal Farmanesia, 2021)
Cooking oil is one of the basic human needs as a good processing media. The repeated use of cooking oil by heating at hight temperatures will produce aldehydes,ketones, hydrocarbons, alcohol and rancid odors, which will affect the quality and nutrition of fried foods. An alternative in the form of processing used cooking oil is through the process of adsorption by activated carbon from bark of zalacca fruits. This study aims to make activated carbon from the bark of zalacca fruit in accordance with SNI 06-37300-95 to determine the characteristics of water content, volatile matter content, total ash content, and carbon content by studying effect of this type of activator on the efficiency in decreasing the content of free fatty acids in cooking oil that have been established by SNI 7709:2012. Determination of freefatty acid levels was carried out by alkalimetric acid titration method. The measurement process was carried out on a sample of cooking oil before frying, after the first, second and third frying before and after purification using activated carbon from the bark of zalacca fruits. The results showed that the levels of free fatty acids were reduced after purification, i.e. before frying from 0,2601% to 0,1420%, on the first frying from 0,3571% to 0,1961%, on the second frying from 0,4826% to 0,2431%, and on the third frying from 1,3845% to 0,2186%. Based on the results of the study it appears that the use of activated carbon from bark of zalacca fruit which is activated by 0,1 N HCL, to improve the quality of used cooking oil, is very effective in reducing the levels of free fatty acids in cooking oil in accordance with quality standard of cooking oil by SNI 7709:201, which is a maximum of 0,3 %.